Non‐isolated resonant link DC–DC converter for use with GaN devices. Issue 17 (20th May 2019) - Orr, Maria; Finney, Stephen; Holliday, Derrick
Abstract : As new wide band‐gap (WBG) devices are developed and improved, new topologies and control schemes are required to take advantage of the ultra‐fast switching turn on/off speeds that are now available, without the limitations of switching losses and unacceptable EMI from fast switching transitions. This paper presents a non‐isolated DC–DC resonant link converter that allows for soft switching over an extended load range that is particularly suited to GaN devices.